First-principles study of the influence of (110)-oriented strain on the ferroelectric properties of rutile TiO2 - EDERER, CLAUDE (American Physical Society, 2011)
We use first-principles density-functional theory to investigate the softening of polar phonon modes in rutile TiO(2) under tensile (110)-oriented strain. We show that the system becomes unstable against a ferroelectric distortion with polarization along (110) for experimentally accessible strain values. The resulting polarization, estimated from the Born effective charges, even exceeds the bulk polarization of BaTiO(3). Our calculations demonstrate the different strain dependence of polar modes polarized along (110) and (001) directions, and we discuss the possibility of strain engineering the polarization direction, and the resulting dielectric and piezoelectric response, in thin films of TiO(2) grown on suitable substrates.
PUBLISHED
Keywords: Condensed matter physics; Thin films